MANAJEMEN KETATAUSAHAAN DALAM MENINGKATKAN MUTU PELAYANAN ADMINISTRASI - Achruh, Andi; Haslindah, Haslindah; Rasyid, Muhammad Rusydi; Kasmawati, Kasmawati (Universitas Islam Negeri Alauddin Makassar, 2023)
The purpose of this study is to explore the planning, implementation and challenges involved in improving the quality of administrative services at SMK Negeri 1 Sinjai. The research method used was qualitative with a phenomenological approach. Data were collected through interviews, observations, and documentation. The research findings indicated that the planning of administration at SMK Negeri 1 Sinjai involved the formulation of tasks and functions of administrative services, goal setting, job evaluation, resource allocation, procurement of facilities and infrastructure, as well as problem-solving. The implementation of administration was conducted well, starting from planning, execution, management and supervision. Administrative activities included personnel administration, financial administration, data and information administration, facility and infrastructure administration, as well as correspondence and archiving. The challenges in improving service quality at SMK Negeri 1 Sinjai were identified as a lack of human resources in the administrative staff and network connectivity issues, which could hinder the service process at the school. The implications of this study are the functioning of the administration management system, improvement in the quality of school administrative services and the establishment of collaboration among administrators, educators and students in achieving these goals.